Impact Analysis of Education Program, Unemployment Rate, and Income Gap on Social Mobility in Jakarta - Febry Lodwyk Rihe Riwoe; Jan Horas Veryady Purba; Arief Yanto Rukmana; Loso Judijanto (West Science Social and Humanities Studies, 2023)
This research investigates the impact of education programs, unemployment rates, and income gaps on social mobility in Jakarta through a quantitative analysis employing Structural Equation Modeling with Partial Least Squares (SEM-PLS) and regression analysis. The study utilizes a sample of 150 respondents, providing a diverse representation of Jakarta's population across age groups, educational backgrounds, employment statuses, socio-economic strata, and geographical locations. The measurement model demonstrates strong reliability and validity, affirming the robustness of the chosen constructs. The structural model reveals a significant positive relationship between education programs and social mobility, indicating that improved access and quality of education positively influence upward mobility. Additionally, income gaps exhibit a negative association with social mobility, emphasizing the adverse impact of income inequality. Surprisingly, unemployment rates do not emerge as a significant predictor of social mobility within the model. The regression analysis further explores these relationships, providing nuanced insights. The study concludes with policy implications, highlighting the need for targeted interventions in education and income equality to foster social mobility in Jakarta. The findings also call for a deeper understanding of the complex dynamics influencing employment and social mobility in the region.